Effectiveness of Performance Assessment for Civil Servants at The Agricultural Extension Center, Agricultural Extension and Human Resource Development Agency, Ministry of Agriculture of The Republic of Indonesia - Mulkika, Alham Fataka; Rialmi, Zackharia (Jurnal Ilmiah Sumber Daya Manusia, 2024)
This research aims is to analyze the effectivity of work performance appraisal in Performance Appraisal Effectivity (Case Study of Government Employee at Program and Evaluation Division Agricultural Center of Counseling Agency for Agricultural Extension and Human Resource Development Ministry of Agriculture of the Republic of Indonesia. Method used in this research is qualitative with 7 participants. The result shows that the work performance appraisal process in Program and Evaluation Group is working effectively given that 5 indicators which is the appraisal itself, linkages, sensitivity, practically, acceptable is effective and one indicator which is reliability is show ineffective. It is expected that Program and Evaluation Division retain their performance appraisal process and increase the effectiveness by reevaluate the reliability of SKP so that it can bet he single tool to appraise work performance